The Relationship of Human Resource Strategic Partner Role and Job Performance under Mediation of Achievement Motivation Structural Equation Model (Global Journal of Management and Business Research, 2020)
This research explored the relationship among human resource practitioner strategic partner role, achievement motivation and the degree of job performance. The research focus was the human resource management practitioners in enterprises and data were collected through convenience sampling. Eight hundred questionnaires were sent out by e-mail, 198 valid questionnaires were returned (24.75%). The results show that there is a significant influence between the： (1) human resource strategic partner and the job performance and (2) achievement motivation of human resource practitioners and the job performance and also that (3) achievement motivation exists mediating effect and affection is completely mediating effect between human resource strategic partner and the job performance.
Keywords: achievement motivation confirmatory factor analysis human resource strategic partner job performance